Laparoscopic management of common cloaca: Current status. Issue 2 (April 2022) - Pathak, Manish; Saxena, Amulya K.
Summary: Aim: This study reviewed the literature on the laparoscopic management of cloaca. Methods: A Medline and Embase search was performed for "laparoscopy" and "cloaca." Articles for which full-text in English was not available, duplicate articles, and review articles were excluded. Demographic characteristics, duration of follow-up, length of common channel, postoperative complications, and functional outcomes were analyzed. Results: The database search retrieved 81 articles after excluding unrelated articles and identified new articles through cross-referencing 14 articles (72 patients) for this review. The rectal pouch was situated below the pubococcygeal (PC) line in three patients. In all other patients, the rectum was located above the PC line. Only the rectal component of the malformation was repaired laparoscopically in 80% (58/72). Fourteen patients underwent laparoscopic mobilization of the rectum and urogenital component. The length of the common channel was more than 3 cm in all these fourteen patients. The most common complication was rectal prolapse (n = 11). Functional evaluation by Krickenbeck scoring system was reported in 32 patients, of which 6/32 (18.75%) had fecal soiling > Grade 2 . Discussion: Until recently, laparoscopy for the common cloaca was almost exclusively used in patients with low urogenital sinus with high rectal pouch. Moreover, only the rectal component was repaired laparoscopically. Recently, laparoscopic rectal mobilization and urogenital separation was described for patients with common channel length ≥3 cm. It has been reported that laparoscopic vaginal mobilization is easy and more complete by this technique and may avoid vaginal replacement in most of these patients with the long common channel. However, only two studies have reported this technique, and its reproducibility and long-term results are still awaited. Another interesting observation was the increasing use of urethral length along with common channel length in determining the appropriate procedure for the patients with common cloaca. Recent studies propose that the urogenital separation technique be preferred over urogenital mobilization in patients with the short urethra. Nonetheless, we still don't have long-term comparative data to demonstrate that the functional outcomes are better with this new algorithm. We conclude that the persistent cloaca needs an individualized approach, and laparoscopy can be utilized to mobilize the high rectum and is also helpful for the urogenital separation in patients with common channel length >3 cm. However, at present, there is no conclusive evidence to support that laparoscopic repair has a better functional outcome than the open approach.